2010
DOI: 10.1136/qshc.2008.031641
|View full text |Cite
|
Sign up to set email alerts
|

A rapid admission protocol to reduce emergency department boarding times

Abstract: Institution of a rapid admission protocol successfully reduced overall EDBT at our institution, although few gains were noted for patients with a telemetry or ICU destination. In total, the intervention saved 27 884 h, or 1161 emergency department patient-days, over the course of a single year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…While the improvement in LOS observed in the current study was much greater (90 minutes), our study was conducted in a higher volume ED following a more comprehensive process change and intervention, which may explain this difference. A second rapid admission process study, reported by Amarasingham et al, used standardized admission holding orders to achieve significant reductions in ED boarding time (360 minutes vs. 270 minutes, p < 0.001) and in the time to admission order placement (210 minutes vs. 75 minutes, p < 0.001) . Howell and colleagues studied another unique intervention, a telephone‐based consultation between emergency physicians and in‐hospital hospitalists for admitted patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the improvement in LOS observed in the current study was much greater (90 minutes), our study was conducted in a higher volume ED following a more comprehensive process change and intervention, which may explain this difference. A second rapid admission process study, reported by Amarasingham et al, used standardized admission holding orders to achieve significant reductions in ED boarding time (360 minutes vs. 270 minutes, p < 0.001) and in the time to admission order placement (210 minutes vs. 75 minutes, p < 0.001) . Howell and colleagues studied another unique intervention, a telephone‐based consultation between emergency physicians and in‐hospital hospitalists for admitted patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that interventions alone are insufficient for achieving high quality improvement rates 25 26. A similar study on reducing emergency admission times applied Kotter's change management model 27. The rapid admission protocol used differs greatly from the Big Squeeze interventions, yet there is a remarkable similarity in their change management approach and engagement of clinician opinion leaders and multidisciplinary teams.…”
Section: Discussionmentioning
confidence: 99%
“…Although the practice of EPs writing holding orders has not been shown to improve patient safety, it has certainly been shown to reduce the length of stay in the ED. [12][13][14][15][16] We know from robust crowding literature that prolonged length of stay in the ED leads to poor outcomes in elderly, stroke, and critically ill patients. [17][18][19][20][21] Treatment delays lead to increased morbidity and mortality.…”
Section: Againstmentioning
confidence: 99%